134k views
1 vote
Need Help with this please

Need Help with this please-example-1
User Raffaele
by
5.0k points

1 Answer

5 votes

9514 1404 393

Answer:

  • 9x² +6x +1
  • 9x² -1
  • (3x +1)(3x -1)

Explanation:

The first step seems to be to eliminate parentheses:

9x² +6x +1 -6x -2 = ...

The next step is to collect terms:

9x² -1 = ...

Then this special form is factored:

(3x +1)(3x -1) = ...

_____

Additional comment

The identity can also be proved by factoring (3x+1) from both terms on the left:

(3x +1)(3x +1 -2) = ...

Then simplify the second factor:

(3x +1)(3x -1) = ...

User Bizmate
by
5.2k points